Fish‐smart seawalls: a decision tool for adaptive management of marine infrastructure. Issue 5 (7th May 2018) - Morris, Rebecca L; Porter, Augustine G; Figueira, Will F; Coleman, Ross A; Fobert, Emily K; Ferrari, Renata
Abstract : Infrastructure is increasingly being built in marine habitats, with extensive ecological consequences for benthic and fish assemblages alike. The practice of ecological engineering attempts to mitigate the negative impacts of infrastructure through the design of artificial structures that benefit both humans and nature. Although research has primarily focused on the benefits for invertebrates and algae, fish also respond to changes in habitat complexity and benthic biodiversity. We surveyed the scientific literature on natural and artificial reefs to identify key habitat features that fish respond to, and propose a decision tool for ecologists and managers to tailor the structural complexity of marine infrastructure for fish. Inevitably, natural habitats will increasingly be replaced with artificial ones, making ecologically sensitive designs essential for maintaining biodiversity and ecosystem services. Using lessons from natural and artificial reefs, we show that existing and new infrastructure could be designed not only to reduce negative impacts but also to foster positive effects on fish assemblages.